Functional Neurorehabilitation and Stem Cell Therapy in Canine Degenerative Myelopathy - Dias, Inês da Silva Ferreira (2020)
Canine degenerative myelopathy is a progressive and fatal neurodegenerative disease with an adult-onset, is described in several breeds and currently doesn’t have an effective treatment. Some forms of amyotrophic lateral sclerosis in humans have homology to degenerative myelopathy, sharing a mutation in the superoxide dismutase 1 (SOD1), which is considered a risk factor to the development of the disease. Functional neurorehabilitation is a modality of restorative neurology and has a fundamental role in neurologic patients. Furthermore, mesenchymal stem cells, due to its differentiation, immunomodulation and regeneration capacity, are an interesting therapeutic option for diverse neurodegenerative conditions. The present study was carried out in Hospital Veterinário da Arrábida, Centro de Reabilitação Animal da Arrábida and Veterinary Medicine School of Lisbon University. The main aim was to evaluate the therapeutic potential of adipose-derived mesenchymal stem cells (MSC) associated with an intensive protocol of functional neurorehabilitation (FNR) in degenerative myelopathy affected dogs. For such, a sample of ten dogs with a diagnosis of exclusion of degenerative myelopathy was selected, four constituted the control group and performed a physical therapy protocol and the other six comprised the study group and were submitted to a stem cell based protocol (MSC and FNR). The results revealed an increase in survival time of the study group’s animals comparing to the ones in the control group. The average survival time since the beginning of physical therapy protocol for the control group was 15 weeks, in contrast with the study group, in which a dog survived 36 weeks and another 88 weeks (death from clinical occurrence) since the initiation of stem cell based protocol. Additionally, two animals in the study group had follow-ups for 88 and 91 weeks, still with acquired motor functionality. It was also possible to verify that 67% of study group’s animals improved according to a functional scoring system (FSS), after the stem cells transplantation. In conclusion, the current study reveals a synergetic effect of the stem cell based protocol in canine degenerative myelopathy.